Impact of Turnover Intention on Work Engagement Among Primary and Secondary School Music Teachers: A Moderated Mediation Approach - Li, Biao Guo, Yujie (Journal of Ecohumanism, 2025)
Work engagement refers to the sustained and active involvement of primary and secondary school music teachers. This study investigated music teachers in Chongqing, examining how turnover intention influences work engagement and exploring the moderating and mediating roles of self-efficacy and educational background (specifically, whether teachers were trained in normal schools). Using a turnover intention scale, a self-efficacy scale, and a work engagement scale, the study found that (1) self-efficacy partially mediates the relationship between turnover intention and work engagement, and (2) educational backgrounds in normal schools moderate this mediation. These findings shed light on the mechanisms through which turnover intention affects work engagement and provide a basis for strategies to enhance the work engagement of primary and secondary school music teachers.